Influência do treinamento sobre a ativação neuronal hipotalâmica induzida pelo exercício físico - Henrique Pereira Santiago (2011)
Aim: to assess whether the alterations induced by physical training on heat balance are followed by modification in neuronal activation within the hypothalamus as a result of graded exercise until fatigue. Material and methods: Wistar animals, aging between 3-4 weeks, were divided in: (1) trained group (T); (2) untrained group (UT); and (3) naïf group. The physical training protocol consisted of running during 8 weeks, 5 days a week. The exercise intensity and duration were gradually increased until the animals reached the velocity of 25 m/min during 60 minutes. After the physical training period, the animals of the T and UT groups were submitted to a session of graded exercise until fatigue (starting at 10 m/min, 1 m/min increment every 3 min until fatigue, 5% inclination of the treadmill). While the animals performed such graded exercise protocol, body (Tb) and tail (Ttail) temperatures, as well as total time of exercise until fatigue were registered. Workload, body heating rate, heat storage and body temperature threshold for tail vasodilation (TTbV) were determined from the data obtained. Ninety minutes after finishing the graded exercise session, the animals brains were removed and prepared for immunohistochemistry analysis. Fos immunomarcation was carried out in the following hypothalamic areas: paraventricular nucleus of the hypothalamus (PVN), medial preoptic nucleus (MPO) and median preoptic nucleus (MnPO). Results: as expected, T animals had higher time of exercise until fatigue (71.0 ± 2.6 min, T vs 38.6 ± 1.9 min, UT, p < 0.01) and an increase of 110% in the workload performed (p < 0.01) in comparison with UT animals. Nevertheless, Tb and Ttail variation during graded exercise was similar between groups. A reduction of 0,6°C in the TTbV was shown by T animals (p < 0,01) when compared with UT rats. Such effect was possibly responsible for the lower body heating rate and decreased ratio between heat storage and the workload performed by T animals (Body heating rate: 0.019 ± 0.002 °C.min-1, T vs 0.030 ± 0.005 °C, UT, p < 0.04; Heat storage/workload: 18.18 ± 1.65 cal/Kgm, T vs 31.38 ± 5.35 cal/Kgm, UT, p < 0.03). Physical training increased by 112% the number of c-Fos immunoreactive neurons in the PVN, by 90% in the MPO and by 65% in the MnPO after graded exercise, in comparison with UT group (p < 0.01). It should be emphasized that c-Fos immunomarcation within these nuclei was also higher in T and UT animals in comparison with the naïf group (p < 0.01). The activation of the PVN, MPO and MnPO was directly associated with the workload performed by the animals during graded running (PVN: r = 0.97, p < 0.01; MPO: r = 0.86, p < 0.01; MnPO: r = 0.77, p < 0.05). Conclusions: the data indicate that physical training enhances neuronal activation within the PVN, MPO and MnPO induced by graded exercise. Such increased activation is related with the improvement of exercise performance and probably contributes to the development of heat balance through heat loss enhancement, since the ratio between heat storage and workload was 72% lower for T animals.